A COUNSELING USING EDUCATIONAL VIDEOS ON THE READINESS OF YOUNG WOMEN TO BECOME MOTHERS-TO-BE - Junengsih junengsih; Yudhia Frathidina; Hetty Astri; Widyo Nurgoho (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2022)
Adolescent girls as prospective mothers have the risk of pregnancy and childbirth and are exposed to other health problems that have an impact on mental health, economic conditions and social welfare in the long term. Pandemic conditions have limited access for adolescents to health services and information, including health education. Objectives: This study aims to determine the effect of educational videos on the level of knowledge and attitudes of young women about readiness to become healthy mothers-to-be. Methods: This study uses quantitative research, the type of research is quasi-experimental with a pre-test-post-test control group design, in this study using two groups. non parametric test that is Wilcoxon test. The test used was non-parametric for the two groups that were not paired, namely the Mann Whitney test. Results: there was a significant difference in the mean score of knowledge (p = 0.00001 ) and attitude (p = 0.0001) of young women in the post test - pre test measurement between treatment group and control group. There is a higher score difference for the knowledge and attitudes of young women who are given intensive counseling using educational videos in readiness to become healthy mothers-to-be. Conclusion: the knowledge and attitude scores of young women intensively using educational videos on readiness to become healthy mothers for young women were significantly higher than those who were not given intensive counseling.